"I Can Go Slapsticks": Humor as Humanizing Pedagogy for Science Instruction With Multilingual Adolescent Immigrant Learners. Issue 1 (November 2022) - Qin, Kongji; Beauchemin, Faythe
Research shows that humor can play an important role in students' language learning and literacy development. However, studies on how teachers intentionally enact humor as a pedagogical tool are still limited. This classroom discourse study examines the interactional construction and pedagogical functions of humor in one U.S. multilingual high school science classroom. Drawing on the theoretical frameworks of languaging and affect, we took a discourse analytic approach to analyze classroom interactions and interview data to examine how the teacher used humor as humanizing pedagogy. We illustrate that the teacher held a humanizing teaching approach to working with immigrant students and viewed "slapstick humor" as part of his humanizing pedagogy. He co-constructed humor with his multilingual students in classroom interaction, and his pedagogical humor worked towards simultaneously humanizing learning, teaching scientific content, and building authentic caring relationships with students through care and empathy. We conclude the article with a discussion of the implications of this study for the research and practice of using humor in language and literacy classrooms with immigrant multilingual students.